Transendensi dalam Novel Advencer Si Peniup Ney Karya Faisal Tehrani - Mohamad Yazid Abdul Majid; Khazri Osman; Rosni Samah; Aishah Isahak; Wan Azura Wan Ahmad; Hanis Sofiya Mohd Solihin (NUNGEMILANG ENTERPRISE, 2025)
Indexed Publication (Tier 3)